Perancangan Tampilan Antarmuka pada Aplikasi Selfqure dengan Menerapkan Metode Design Thinking - I Gede Arisudana Samanjaya; Ida Bagus Gede Dwidasmara (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2023)
Mental health disorders in adolescents are influenced by factors such as social pressure, identity exploration, violence, harsh parenting, and socio-economic problems. The lack of understanding and stigma surrounding mental health issues often leads adolescents to avoid discussing their problems, resulting in potential risks to their well-being. To address this, the development of mobile applications like